Simplify the expression:

(8s+2)(2)=

1 answer

To simplify the expression \((8s + 2)(2)\), you can use the distributive property (also known as the distributive law of multiplication over addition). This means you multiply each term inside the parentheses by \(2\).

Let's perform the simplification step-by-step:

\[ (8s + 2)(2) = 8s \cdot 2 + 2 \cdot 2 \]

Now calculate each term:

  1. \(8s \cdot 2 = 16s\)
  2. \(2 \cdot 2 = 4\)

Now, combine these results:

\[ 16s + 4 \]

So, the simplified expression is:

\[ \boxed{16s + 4} \]